THE INFLUENCE OF CAFE ATMOSPHERE, MENU VARIETY, AND PRICE ON CUSTOMER SATISFACTION - Arnando, Ria; Purnomo, Agus (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the influence of cafe atmosphere, menu variety, and price on customer satisfaction at Cafe Kopi Kita in West Tulang Bawang. The rapid growth of the culinary sector has led to intense competition, requiring business owners to understand the factors driving customer satisfaction. This research employs a quantitative approach. The population includes all customers of Cafe Kopi Kita, with a sample of 138 respondents selected using purposive sampling. Data were collected via questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that cafe atmosphere and price have a significant partial effect on customer satisfaction. However, menu variety does not significantly influence satisfaction. Simultaneously, cafe atmosphere, menu variety, and price significantly affect customer satisfaction. The Adjusted R Square value of 0.436 indicates that these variables explain 43.6% of the variation in customer satisfaction. This suggests that to maximize satisfaction, the management should focus more on enhancing the physical environment and maintaining competitive pricing strategies rather than excessively expanding menu variations.